Analisis faktor yang mempengaruhi keputusan investasi generasi millenial di surabaya - Nabila Rahma (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This study aims to determine the effect of financial literacy, financial behavioral, risk perception, risk tolerance, herding, and anchoring on investment decisions in the millennial generation in Surabaya. The type of data used is quantitative data sourced from primary data through questionnaires. The population in this study is the millennial generation in Surabaya which included the millennial generation at Surabaya city with the category of the highest number of millennial generation in each region of 1,155,598 Surabayans. The sampling technique used snowball sampling and purposive sampling which was taken evenly throughout the Surabaya area, both in North Surabaya, South Surabaya, East Surabaya, West Surabaya and Central Surabaya and 220 were obtained as samples in this study and the criteria of sampling is investors who are millennials domiciled in the city of Surabaya, have securities accounts, have traded stocks at least 1x. Data were analyzed using multiple linear regression and calculated using IBM SPSS 26. The results showed that risk perception, herding, and anchoring had a significant and positive effect on investment decisions. Meanwhile, financial literacy, financial behavioral, and risk tolerance have no significant effect on investment decisions. Therefore, the millennial generation in Surabaya are expected to improve it’s predictions on existing investment risks in order to be able to make better investment decisions.